2004
DOI: 10.1007/s00115-004-1683-x
|View full text |Cite
|
Sign up to set email alerts
|

Rezidivierende zerebrale Ischämien bei zerebraler Vaskulitis im Rahmen eines inkompletten POEMS-Syndroms mit M. Castleman

Abstract: The POEMS syndrome is a multisystem disorder characterised by polyneuropathy, organomegaly, endocrinopathy, plasma cell dyscrasia and skin changes. A coincidence with angiofollicular lymphoid hyperplasia (Castleman's disease) exists in about 60% of all cases. The POEMS syndrome may be associated with macroangiopathy and acute vascular obliterations. Most case reports refer to involvement of the coronary and lower limb arteries. There are only few reports dealing with cerebral strokes and POEMS syndrome. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…However, the frequencies of stroke risk factors such as diabetes mellitus, hypertension and atrial fibrillation occurred in our study are similar to or even lower than those in stroke registries [ 54 , 55 ]. In accordance with previous literature, the preponderance of multiple cerebral vessel lesions and coexistence of extracerebral vessel disease in patients of POEMS without stroke risk factors are also more common than those reported in stroke registries [ 13 - 14 , 22 - 24 , 27 - 28 , 38 ]. This phenomenon may suggest that POEMS syndrome has a predisposition towards large-vessel vasculopathy which could only be confirmed by biopsy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the frequencies of stroke risk factors such as diabetes mellitus, hypertension and atrial fibrillation occurred in our study are similar to or even lower than those in stroke registries [ 54 , 55 ]. In accordance with previous literature, the preponderance of multiple cerebral vessel lesions and coexistence of extracerebral vessel disease in patients of POEMS without stroke risk factors are also more common than those reported in stroke registries [ 13 - 14 , 22 - 24 , 27 - 28 , 38 ]. This phenomenon may suggest that POEMS syndrome has a predisposition towards large-vessel vasculopathy which could only be confirmed by biopsy.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, pathologically confirmed vasculitis involving small-sized and medium-sized muscular artery are reported to be directly associated with POEMS syndrome [ 57 , 58 ]. In addition, larger-sized vessels are also suspected to be affected in POEMS syndrome [ 8 , 10 , 22 , 59 ]. Co-existing quasi-moyamoya disease and POEMS syndrome were observed in a patient with sudden-onset intracranial hemorrhage [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rössler M et al reported on a case of young female with POEMS syndrome presented recurrent ischemic stroke due to cerebral vasculitis. In this case, DSA showed the segmental stenosis of proximal ACA [ 9 ]. Garcia T et al described two cases of POEMS syndrome and MCD accompanied with recurrent ischemic stroke, in which DSA showed diffuse non-atherosclerotic segmental stenosis of the intracranial arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Among these inflammatory biomarkers, IL-6 is well known to play an important role in acute inflammatory response triggered by cerebral ischemia, and an elevated blood IL-6 concentration is associated with poor outcome after stroke [ 11 ]. Moreover, a higher level of serum IL-6 is also associated with an increased risk of recurrent vascular events after stroke [ 9 ]. Despite these conclusive findings in both acute and chronic phases that clearly indicate an important role of IL-6 in stroke patients, these associations are not fully understood.…”
Section: Discussionmentioning
confidence: 99%